From an aesthetic point of view : Philosophy, Art and the Senses. - Osborne, Peter; Agacinski, Sylviane; Batchelor, David; Bernstein, Jay; Caygill, Howard; Garcia Düttmann, Alexander; Menke, Christoph; Merck, Mandy; Rancière, Jacques; Rée, Jonathan (London : Serpent's Tail London, 2000)
Contemporary visual art stands on the ruins of beauty. What is the place of the aesthetic in the experience of such art ? And how has it changed in the two hundred years since the emergence of the modern conception of art as the object of a distinctive kind of pleasure in form ? The essays in this volume, by philosophers and art theorists from Britain, France, Germany and the USA, investigate the changing role of the aesthetic in art. In writing that is both lucid and challenging, the contributors make clear that the importance a society places on art and the aesthetic is a barometer of its very health.
Biog. auters p. 183-184
Engels
boek
Keywords: Sherman, Cindy; Rauschenberg, Robert; LeWitt, Sol; Richter, Gerhard; Klein, Yves; Weiner, Lawrence; Kawara, On; Turrell, James; Kapoor, Anish